2001
DOI: 10.1191/09596830195762
|View full text |Cite
|
Sign up to set email alerts
|

Proposed changes in seasonality of climate during the Lateglacial and Holocene at Lake Zeribar, Iran

Abstract: Calcareous sediments spanning the last 13 ka fromn I,ake Zeribar, western Iran, were sampled for stable-isotope analysis as a means of augmenting earlier climatic interpretations based on polleni and macrofossils. The Lateglacial period was cold and dry, suLpporting semi-desert vegetation and highly concentrated lake water. Low evaporation rates due to the cold resulted in long residenice times and high lake stands. Durinig the earlv Holocene, the upland vegetation changed to a pistachio-oak savanna as low tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
212
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(236 citation statements)
references
References 34 publications
20
212
1
3
Order By: Relevance
“…These values are significantly higher than the range of precipitation values specified by Stevens et al (2001) i.e. -10 to -14‰ for Zeribar.…”
Section: Zeribarmentioning
confidence: 60%
See 1 more Smart Citation
“…These values are significantly higher than the range of precipitation values specified by Stevens et al (2001) i.e. -10 to -14‰ for Zeribar.…”
Section: Zeribarmentioning
confidence: 60%
“…Periods of net water loss , 1997) showed that relative humidity was an important driver of P:E (specifically E) and suggested that the  18 O c record could be used to quantitatively reconstruct relative humidity through time. Stevens et al (2001) interpreted changes through the Holocene part of the Zeribar  18 O c record as due to changes in the predominant seasonality of rainfall at the site. They showed that increases in the percentage of precipitation falling in the winter months would lead to more negative isotope values of the annual weighted precipitation.…”
Section: Interpretationsmentioning
confidence: 99%
“…During interglacial peaks, maximum tree pollen percentages reflect warm conditions and higher precipitation from the mid-latitude westerly system. Changes in seasonality were proposed by several authors to explain Holocene climate in the region (Stevens et al, 2001(Stevens et al, , 2006Magny, 2007;Tzedakis, 2007;Peyron et al, 2010;Djamali et al, 2010). At Yammoûneh, sharp δ c increases in phase with arboreal pollen peaks, attributed to enhanced seasonal thermal and hydrological contrasts, suggest that the hypothesis of seasonal changes is valid for older interglacial stages (e.g., MIS 5.5 and MIS 5.1).…”
Section: Comparison With Other Ems Recordsmentioning
confidence: 99%
“…1; Eastwood et al, 2007), or changes in precipitation seasonality (at Lakes Zeribar and Mirabad, NW Iran, Fig. 1; Stevens et al, 2001Stevens et al, , 2006). As discussed above from both pollen and isotope data, we favour the hypothesis of seasonal increased hydrological and thermal contrasts with wet cool winters, possibly a longer rainy season, and very dry warm summers generating strong evaporative effects in both the drainage area and the waterbody.…”
Section: Relationships Between Individual Proxiesmentioning
confidence: 99%
“…However, longer-term reconstructions of climate change in the Holocene are of limited number and are spatially and temporally restricted (Bar-Matthews et al 1998, Goodfriend 1999, Schilman et al 2001, Stevens et al 2001, Roberts et al 2001, Kashima 2002, Wick et al 2003, Jones et al 2005, Eastwood et al 2007). Due to generally unfavourable climatic conditions for peat formation and human destruction of mires, Turkish peatlands are rare, covering perhaps 30 Km 2 (Çayci et al 1988(Çayci et al , Őz 1996(Çayci et al , Byfield and Őzhatay 1997.…”
Section: Introductionmentioning
confidence: 99%